The levels of ghrelin, leptin, TNF-?, and IL-6 in liver cirrhosis and hepatocellular carcinoma due to HBV and HDV infection - Ataseven, Huseyin; Bahcecioglu, Ibrahim Halil; Kuzu, Nalan; Yalniz, Mehmet; Celebi, Selman; Erensoy, Ahmet; Ustundag, Bilal (Hindawi Ltd, 2006)
Background/Aim. Malnutrition, a common problem in liver cirrhosis and HCC, may readily deteriorate the clinical functions with resultant poor prognosis. Beside the hyper catabolic state frequently encountered in chronic liver disease and HCC, anorexia and reduced food intake also worsen the malnutrition. The recently discovered peptide hormone ghrelin acts as a counterpart of leptin in regulation of food intake and fat utilization. The aim of the present study was to investigate the ghrelin and leptin levels in cirrhosis and HCC due to hepatitis B and D viruses, and the association of ghrelin and leptin with TNF-alpha, IL-6 and the severity of the disease. Materials and methods. We measured serum ghrelin, leptin, TNF-alpha, and IL-6 levels using specific immunoassay in 45 patients (23 cirrhosis, 22 HCC) with HBV and/or HDV and in 25 control subjects. Results. In comparison to controls, serum ghrelin, TNF-alpha, and IL-6 levels were significantly higher in cirrhosis and HCC (P <.05), whereas serum leptin levels were found decreased (P <.05). There was a positive correlation between ghrelin and TNF-alpha, and a negative correlation between leptin and TNF-alpha (P <.05). Conclusion. In cirrhosis and HCC due to HBV or HDV, serum ghrelin levels were increased with a corresponding decrease in serum leptin concentrations, acting as a physiological counterpart of ghrelin. The increasing of ghrelin is more prominent in Child C cirrhosis and the level was correlated with TNF-alpha. The presence of nutritional and metabolic abnormalities, including malnutrition, in cirrhosis and HCC may, at least partly, elucidate high ghrelin and low leptin levels. Copyright (c) 2006 Huseyin Ataseven et al.
Keywords: Tumor-Necrosis-Factor; Serum Leptin; Dependent Alterations; Energy-Expenditure; Risk-Factors; Malnutrition; Cytokine; Peptide; Interleukin-6; Metabolism